Common Fixed Point Theorems For Single And Seta Valued Maps In nona Archimedean Fuzzy Metric Spaces (Global Journal of Science Frontier Research, 2012)
The intent of this paper is to establish a common fixed point theorem for two pairs of occasionally weakly compatible single and set-valued maps satisfying a strict contractive condition in a non -Archimedean fuzzy metric space.
Keywords: Occasionally weakly compatible maps; implicit relation; common fixed point theorems; Strict contractive condition; fuzzy metric space